PRECISION PEDAGOGY: FOSTERING EXPERTISE IN NURSING STUDENTS’ PHYSICAL EXAMINATION SKILLS USING SIMULATION - Elif , Yılmaz; Murat , Demir; Karaaslan, Aylin (Research Journal of Health, Medicine and Nursing, 2024)
In the ever-evolving clinical landscape, nursing's role has expanded to encompass advanced cognitive, affective, and psychomotor skills, owing to rapid technological advancements (Morgan, 2006). A crucial facet of nursing practice is the mastery of physical examination skills, making the teaching of these skills an integral component of nursing education programs (Birks, James, Chung, Can’t, & Davis, 2014). However, the acquisition and retention of these skills’ present considerable challenges (Kantak & Winstein, 2012). Nursing education places a strong emphasis on fostering competence and ensuring the quality of patient care and safety (Edeer & Sarıkaya, 2015). To achieve this, students must gain valuable, high-quality experiences during their education (Goldsmith, Stewart, & Ferguson, 2006). Unfortunately, the increasing number of nursing students and the limited availability of educators and clinical placements have led to constraints on the time students can spend enhancing their clinical skills (Kaddoura, 2010; Yuan, Williams, Fang, & Ye, 2012). This limitation hinders students' ability to bridge the gap between theoretical knowledge and clinical practice, recognize critical patient indicators, and refine their caregiving abilities (Norman, 2012; Tanner, 2006; Yuan et al., 2012).